PENERAPAN TEKNOLOGI KOMPUTER DALAM SISTEM PEMBELAJARAN BACA TULIS ALQURAN BAGI GURU-GURU TKA-TPA - Nurkholis, Nurkholis; Mutaqin, Mutaqin; Sudiyatno, Sudiyatno (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
The target of implementing a public service program was giving themanagement and teaching staffs of taman pendidikan Al-Qur'an (TPA) and taman kanak-kanak Al-Qur'an  (TKA), schools for elementary school and kindergarten students' education in the Al-Quran,  knowledge of and insight in applying computer technology in conducting the teaching-learning process and improving their skills and abilities in operating computer-assisted program packages of education in the Al-Qur'an.The methods  used  in the activities of the public service programwere, among others,  lectures,  discussions, question-and-answer sessions,demonstrations, and practice, the activities being essentially training activi ties enabling participants to acquire knowledge and skills. The training ma terials delivered were related to the topics of introduction to computer ope ration based on the Windows system of operation, the program package of the Holy Qur'an, and Islamic children's education.The training activities have resulted in the TPA and TKA manage ment and teaching staffs participating in the activities becoming better in their knowledge of  and  insight  in applying computer technology  in  the course of improving the quality of the teaching-learning process of readingthe Al-Qur'an and writing texts taken from it in the educational institutions where they work. They have indeed been greatly in need of the training ma terials. Their  skills  and abilities  in operating computer-assisted program packages of education in the Al-Qur'an have also become better than those possessed before participating in the training. Evaluation on the results of the public service program  indicates that on the average the participants' knowledge and skills have risen from 34.44% into 78.66%, which implies an increase of 44.22%.Keywords: computer technology, reading and writing texts taken/rom   theAl-Qur'an